Mechanisms and Therapeutic Potential of Natural Polysaccharides in Alleviating Depression via Microbiota-Gut-Brain Axis - Chhabra, Colin; Oger, Philip; Imran, Hafiz (Journal of Green Energy and Environmental Engineering, 2025)
Depression is one of the most burdensome mental disorders worldwide, and its clinical management still faces challenges such as low treatment response rates and frequent adverse effects associated with conventional pharmacological agents. Recent research on the microbiota-gut-brain axis (MGBA) has demonstrated that gut microbiota and their bioactive metabolites play a crucial regulatory role in neurological function by orchestrating neuro-endocrine-immune pathways. These findings provide new potential targets for therapeutic interventions in depression. This review summarizes current research on natural polysaccharides that modulate the gut microbiota and alleviate depression, systematically elucidating the multi-modal antidepressant mechanisms mediated via MGBA, and provides new insights for advancing strategies for the prevention and treatment of depression.